Some Remarks on the Core of a "Large" Economy - Khan, M. Ali (Econometrica, 1974)
The core is the set of all allocations that cannot be blocked by any coalition no matter how improbable is its formation. Extending the insights of the Continuum School, this article shows that restrictions placed on the formation of coalitions do not enlarge the core very much if the finite economy is large. (Из Ebsco)